The effect of the galaxy environment on the size and structure of galaxies - Maltby, David Terence (2013)
In this thesis, we explore the effect of the galaxy environment on the physical size and structure of the stellar distribution for relatively local galaxies (z < 0.3) using Hubble Space Telescope/Advanced Camera for Surveys imaging and data from the Space Telescope A901/2 galaxy evolution survey (STAGES).